Prevalence and specificity of RBC alloantibodies in the general hospitalised population in Guangxi. Issue 5 (1st July 2015) - Mo, Z.; Li, H.; Huang, L.; Jiao, W.
SUMMARY: Objectives: The aim of this work was to investigate the prevalence and specificities of red blood cell (RBC) alloantibodies in the general hospitalised population in Guangxi, China. Background: Alloimmunisation to RBC antigens is a major complication of transfusion therapy, and alloantibodies pose many clinical problems such as blood transfusion–related adverse reactions. The frequency and specificity of erythrocyte alloantibodies were different in populations from different geographic areas and races. However, the data on alloantibodies in the Guangxi population are limited; thus, we aimed to investigate them in this study. Methods: Erythrocyte request records of Guangxi patients were retrospectively reviewed from January 2013 to February 2014. Data from antibody screening tests for 20 283 patients were retrieved for analysis. Clinical data, including gender, age, medical history, transfusion history, pregnancy history and alloantibody specificity were collected. Results: Data from 20 283 patients were analysed, and a total of 166 alloantibodies were identified in 150 patients (0·74%). The most frequent alloantibodies were anti‐E (39·76%), anti‐Mi a /Mur (11·45%), anti‐c (10·84 %), anti‐Le a (8·43%) and anti‐M (6·63%). Three cases of anti‐D (1·81%) and two rare cases of anti‐H (1·20%) were also detected. Conclusions: The frequency and specificities of erythrocyte alloantibodies among hospitalised patients in Guangxi were different from those in other Chinese populations and Caucasians, although the alloantibodies against the antigens of the Rh system are still common. Anti‐E and anti‐Mi a /Mur were more common in Guangxi patients, but anti‐K and anti‐D, which are prone to develop in Caucasians, were less likely to develop in our patients.